2013
DOI: 10.1097/01.brs.0000435027.50317.d7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pressure Pain Threshold in Patients With Chronic Nonspecific Low Back Pain

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
4
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 34 publications
7
62
4
9
Order By: Relevance
“…PPT was found to decrease as a result of CLBP; however, it was not detected as a predisposing factor for the development of low back pain in the follow-up study by O'Neill et al 6 Furthermore, in the study conducted by Imamura et al, 5 PPT values of myotomes, sclerotomes and dermatomes between L1 and S3 segments were evaluated and lower PPT values were reported in CLBP patients. They proposed that the hyperalgesia in the painful area may be a result of several mechanisms such as central nervous system sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPT was found to decrease as a result of CLBP; however, it was not detected as a predisposing factor for the development of low back pain in the follow-up study by O'Neill et al 6 Furthermore, in the study conducted by Imamura et al, 5 PPT values of myotomes, sclerotomes and dermatomes between L1 and S3 segments were evaluated and lower PPT values were reported in CLBP patients. They proposed that the hyperalgesia in the painful area may be a result of several mechanisms such as central nervous system sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limited number of studies emphasized on the perception of pain and pain threshold of patients with chronic low back pain (CLBP). 4,5 The association between high pain sensitivity in chronic pain conditions including low back pain was investigated, and it was reported that the pressure pain threshold (PPT) decreased due to long lasting pain. 4,6 One of the proposed mechanisms of pain sensitivity was sensitization of the central nervous system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as studies that utilize intramuscular EMG in the trunk do not routinely quantify the level of pain associated with this methodology, it is unclear whether discomfort following insertion is of sufficient intensity or duration to elicit changes in motion in the trunk during motor activities after the electrode insertions. Individuals with a history of LBP may have a more pronounced response to the insertion of intramuscular electrodes than healthy individuals due to elevated fear avoidance behaviors or lowered pain thresholds (Imamura et al, 2013;Wand et al, 2011). Therefore, it is also important to determine if the magnitude of any change in motion in response to electrode insertion is the same in healthy individuals and individuals with a history of LBP.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research exists to show that individuals with CLBP have lower pain thresholds to pressure or punctate stimuli compared to pain-free controls [14][15][16][17] which suggests that CLBP is associated with a state of enhanced pain sensitivity. In addition, recent advancements in dynamic experimental paradigms have shown that CLBP may also be associated with systemic changes in pain modulation.…”
Section: Introductionmentioning
confidence: 99%